(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
In this paper, the hydraulic analysis and evaluation of three head loss techniques (Hazen-Williams, HW, Chezy-Manning, CM and Darcy-Weisbach, DW) available for utilization at the EPANET platform were evaluated. The Elizade University (EU), Ilara- Mokin network was analysed using EPANET software. The hydraulic properties (flow rate, head-loss, Reynold’s number, friction factor and velocity of discharge) were determined using the three head-loss techniques available at the EPANENT software and Microsoft Excel Solver (MiExS) as the standard (based on previous studies). The friction factors (ff) obtained from these techniques were evaluated using relative and square errors. The study revealed that the elevations at the EU were between 339.1 m and 390 m, the diameters of the pipes were between 150 mm and 50 mm and water withdrawals were in the range of 480l/s to 30l/s. The discharges through the pipes were from 2.0 x 101 l/s to 3.545 x 103 l/s, the ff of these pipes ranged between 0.019 and 0.012 for MiExS and DW, between 0.0012 and 0.025 for HW and between 2.03 x 10 5 and 3.21 x 105 for CM. Effects of techniques on the ff were significant at 95 % confidence level (F3,160 = 803.06; p of 3.45 x 10-96, which was less than 0.05). It was concluded that DW performed better than HW and the least performed technique was CM. It was suggested that CM at EPANET should not be used for pressurised pipelines hydraulically and caution is required in its utilization for pressurised pipe network.